The Effect Of Work Communication And Job Satisfaction On Teacher Performance At State Senior High School 1 Kutambaru, Langkat Regency - Dian Oktavianti; Kiki Farida Ferine; Ahmad Aswan Waruwu (Universitas Dehasen Bengkulu, 2026)
The research analysis aims to determine the influence of work communication and job satisfaction on teacher performance at SMA Negeri 1 Kutambaru, Langkat Regency. The research approach used is a quantitative associative approach. This study employed multiple linear regression analysis with a sample of 30 respondents. Primary data collection used a questionnaire. The results of the study indicate that the work communication variable has a t count of 4.358 and a t table of 2.051831, so t count > t table (4.358 > 2.051831) with sig. 0.000 < 0.05 so that the results of the study accept H1. It can be explained that the work communication variable (X1) influences the teacher performance variable (Y). The job satisfaction variable has a t count of 4.274 and a t table of 2.051831, so t count > t table (4.274 > 2.051831) with sig. 0.000 < 0.05 so that the results of the study accept H2. It can be explained that the job satisfaction variable (X2) influences teacher performance (Y). The results of this study indicate that the f count value = 15.196 > f table 3.35 with sig. 0.000 < 0.05. So it can be concluded that H3 is accepted. Where the work communication variables (X1) and job satisfaction (X2) simultaneously have a positive influence.